Narrative irony in Luke-Acts: the paradoxical interaction of prophetic fulfillment and Jewish rejection - Ray, Jerry Lynn (Mellen Biblical Press series, 1996)
The study shows, through narrative critical methodology, that the author of Luke-Acts sees irony in the events of the church's history, and that this irony is central to his primary theological purpose. The interaction of two prominent Lukan literary motifs, the fulfillment of scriptural prophecy and the Jewish rejection of Jesus and the gospel, produces a paradoxical irony of events that extends through the narrative and serves the author's christological and soteriological purposes. Christologically, the Jewish rejection of Jesus as Messiah demonstrates his messiahship, for it leads to his suffering and resurrection which fulfill the scriptural promises regarding the messianic event. Soteriologically, the Jewish rejection of the gospel actually promotes its worldwide acceptance, thereby fulfilling God's plan to grant salvation to all nations.